(untitled) (Cadernos de Linguagem e Sociedade, 2010)
The aim of this paper is to rethink the concepts of ‘transversality’ (the transversal themes’ approach) and ‘interdisciplinarity’ as they were constructed in the Brazilian National Syllabus and instantiated in two Applied Linguistics studies. From their emergency in an analysis of English teachers’ practical theories, these notions are considered in another study about school practices and reviewed in their epistemological and discursive characteristics.